Rancang Bangun Aplikasi Finding Dosen Untuk Mencari Posisi Dosen FILKOM di Dalam Ruangan Menggunakan Metode Color Radiomap Interpolation - Miftahul Rizki Purwonegoro; Herman Tolle; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The existence of student and lecture is a main component from study in educational institution. Many student who has an obstacle experiences to looking for lectures position in campus. In addition to lecturing, lecture is also have another duties to do Tri Dharma Perguruan Tinggi, it becomes an obstacle for student to looking for lectures position where not always located in their room. In general, to determine someone position using GPS (Global Positioning System), however GPS have also a weakness such as can't determine someone inside the building. This study is to build an application that can find lectures position inside the building using Color Radiomap Interpolation method. Received Signal Strength Indicator (RSSI) from 3 Access Point is used to develop this application. The value from RSSI is converted turn into a color map that used to determine lecture position. This application is developed in two sides where for the lecture is used to change the status to can be found its position, for the students is also can find the lecture and see the position. Determining position with compare training data in the color map by test data when the status from lecturer is changed with collecting the smallest data from the equation of Mean Squared Error. The result is show that all of the requirement can be validated, with with accuracy 90%.